Mechanics of Composite and Multi-functional Materials, Volume 7 Proceedings of the 2015 Annual Conference on Experimental and Applied Mechanics - Ralph, Carter; Silberstein, Meredith; Thakre, Piyush R.; Singh, Raman (Conference Proceedings of the Society for Experimental Mechanics Series, 2016)
Experimental Mechanics of Composite, Hybrid, and Multifunctional Materials, Volume 7  of the Proceedings of the 2015SEM Annual Conference& Exposition on Experimental and Applied Mechanics, the seventh volume of nine from the Conference, brings together contributions to this important area of research and engineering.  The collection presents early findings and case studies on a wide range ofareas, including: Multifunctional Materials Hybrid Materials Novel Composites Nano- and Particle-Reinforced Composites Additive Manufacturing of Composites Digital Imaging of Composites Damage Detection Non-Destructive Evaluation Fatigue and Fracture of Composites Manufacturing and Joining of Composites Advanced Composites Applications.